PRODUK WISATA, KELOMPOK ACUAN DAN LOKASI TERHADAP KEPUTUSAN BERKUNJUNG DI OBJEK WISATA AIR PANAS SEMURUP KABUPATEN KERINCI - Gampo Haryono; Fiqri Erlanda Putra (LPPM - STIE SAKTI ALAM KERINCI, 2023)
This study aims to identify the influence of tourism products, reference groups and location on the decision to visit the Semurup Hot Spring Tourism Object, Kerinci Regency. This research was conducted to test whether there is the influence between variables, specifically to test the hypothesis in the structural equation. The data analysis technique used in this research is Multiple Linear Regression analysis technique. The results showed that tourism products had a significant influence on visiting decisions, as evidenced by t count > t table (2.182 > 1.987934 ) and with a significant value = 0.032 <0.05. The reference group has a significant influence on the visiting decision as evidenced by t count > t table (2,911 > 1.987934) and a significant value = 0.005 <0.05. Location have a significant influence on visiting decisions as evidenced by t count > t table (2.631 > 1.987934) and a significant value = 0.010 <0.05. Tourism Products, Reference Groups and Location have a significant influence on visiting decisions as evidenced by F count > F table (11.240 > 2.710647) and a significant value = 0.000 <0.05.